Understanding how gay men construct ‘good’ chemsex participation using Critical Discursive Psychology - Healy-Cullen S; Shanley A; Noone C (Informa UK Limited, trading as Taylor & Francis Group, 2024)
Research to date has focused on the potential issues arising from chemsex and often seeks to uncover what is ‘wrong’ with those who are motivated to engage in chemsex. Critical chemsex studies reaches beyond this harm-orientated focus and instead adopts a social justice approach that recognises chemsex participants as legitimate sexual citizens. The present study – comprising eight interviews with gay men living in Ireland – is situated within this critical research praxis. Using a critical discursive psychology framework, our analysis demonstrates how participants draw on various interpretative repertoires to discursively negotiate chemsex identities in a bid to position themselves in a culturally intelligible manner. Participants deployed three key repertoires, centred around (i) harm, (ii) essentialism, and (iii) ethics. These repertoires are deployed in an interweaving manner to ultimately construct a dynamic, hierarchal continuum of chemsex participants – from flourishing, to flailing. Our analysis demonstrates how chemsex participants construct ‘other’ chemsex users as ‘flailing’ towards the bottom of the continuum by mobilising repertoires that draw upon prevailing moralistic notions of ‘good’ sexual citizenship. We argue that the mainstream construction of chemsex as inevitably harmful is restrictive and produces a deficit understanding of chemsex participants, and discuss the possibilities for discursively reimagining chemsex participation.
Keywords: Chemsex; harm reduction; gay men; sexual health; drug use